Reflections of Twitter integration in higher education based on an educational experience with student teachers - A. Pérez; G. Tur; A. Darder; V. Marín (Universitat Politècnica de València, 2019)
The use of social media in education has been broadly discussed in the literature and different educational experiences have been proposed in higher education to get students to value them as a powerful aids for self-regulated learning, going beyond being tools for informal communication. A specific field where these experiences have been numerous is initial teacher training, due to the value of social media for professional development, and for their future pedagogical use. In this work the lights and shadows of the use of Twitter for learning in higher education are analysed through a literature review and the exploration of diverse learning designs implemented in consecutive academic years with student teachers. The variations in those designs were planned according the model of design-based research. The objectives of the study that have guided the successive implementations and evaluations of the learning design have enable the data collection to be conducted in a multidimensional perspective, by observing the learners' activity for information management, and concretely, for the selection and sharing of resources, as well as to identify certain difficulties for the real metacognitive activity on learning. The conclusions provide elements of discussion on the implications of the use of social media for learning and offer recommendations for initiatives in institutional contexts and for the design of proposals based on the model of self-regulated learning, whose aim may be the real individual and collective transformation.